Efficacy of herbal medicines in the treatment of acute respiratory infections in real clinical practice - Valery M. Svistushkin; Galina N. Nikiforova; Elena A. Shevchik; Anna V. Zolotova; Anna N. Nikiforova; Dmitrii A. Sivokhin (Consilium Medicum, 2022)
Background. Unreasonable prescription of antibiotics to patients with acute diseases of the upper and lower respiratory tract is a significant problem of modern medicine, as it is associated with a high risk of side effects, an increase in antibiotic resistance and high economic costs. Phytopreparations can help reduce the frequency of inadequate antibiotic prescribing.